1985
DOI: 10.1083/jcb.100.4.1148
|View full text |Cite
|
Sign up to set email alerts
|

Stability and movement of mRNAs and their encoded proteins in Xenopus oocytes.

Abstract: The stability and movement of several polyadenylated (poly A ÷) and nonpolyadenylated (poly A-) mRNAs in Xenopus oocytes have been examined. At least 50% of the poly A ÷ mRNA molecules (9S rabbit globin mRNA, chicken ovalbumin, and lysozyme) were stable in oocytes over a 48-h period, irrespective of the amount injected. About 50% of injected poly A-reovirus mRNAs was degraded within the first 24 h of injection, irrespective of the amount injected, although no further degradation was observed over an additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
(56 reference statements)
2
16
1
Order By: Relevance
“…Transcription of a terminator-less transgene is expected to generate improperly terminated, unpolyadenylated mRNAs that are known to be unstable (Drummond et al, 1985). However, we found that in the sde1-1 mutant background, substantial levels of mostly unpolyadenylated GUS transcripts were detected in the transformants harboring the terminator-less GUS construct (Figures 3B and 5).…”
Section: Discussion Improperly Terminated Unpolyadenylated Transcripmentioning
confidence: 51%
“…Transcription of a terminator-less transgene is expected to generate improperly terminated, unpolyadenylated mRNAs that are known to be unstable (Drummond et al, 1985). However, we found that in the sde1-1 mutant background, substantial levels of mostly unpolyadenylated GUS transcripts were detected in the transformants harboring the terminator-less GUS construct (Figures 3B and 5).…”
Section: Discussion Improperly Terminated Unpolyadenylated Transcripmentioning
confidence: 51%
“…The percentages of globin mRNA that remained stable in stage 4 relative to stage 6 oocytes were 12.8%:5.8%, 3.2%:2.5%, and 98%:75%, respectively, for the three experiments. Coincidentally, these experiments resolve another paradox present in the literature: Drummond et al (19) reported that the majority of globin mRNA injected into stage 6 oocytes is stable, in contrast to the study of Richter and Smith (4). Our current data show considerable variability among oocytes from different females, so that almost any percentage could be obtained, depending on the female donor used.…”
Section: Methodscontrasting
confidence: 51%
“…Previously it has been reported that RNAs diffuse more slowly than proteins in oocytes [47]. Thus, if the injected RNAs and the Hermes protein diffuse independently one would expect Hermes, a relatively small protein, to spread faster through the oocyte than Cy5- nanos1 RNA.…”
Section: Resultsmentioning
confidence: 96%